Transcriptomic analysis of Lacticaseibacillus paracasei Zhang in transition to the viable but non-culturable state by RNA sequencing - Bao, Qiuhua; Ma, Xuebo; Bo, Xiaoyu; Pang, Jing; Dai, Lixia; Wang, Huiying; Chen, Yongfu; Kwok, Lai-Yu (Frontiers in Microbiology, 2023)
Background Some bacteria enter the viable but non-culturable (VBNC) state to survive harsh environmental conditions and external stresses. This alters cell physiology and has implications for the food industry as some bacteria, such as lactobacilli, undergo similar changes during food processing. Methods This study aimed to investigate the transcriptomic changes of a probiotic strain, Lacticaseibacillus paracasei Zhang (L. paracasei Zhang), upon transition to the VBNC state using high throughput RNA sequencing (RNA-seq). Results Bacteria were inoculated into the de Man, Rogosa, and Sharpe medium and maintained at low temperature and pH to induce cell transition to the VBNC state. Cells were harvested for analysis at five stages of VBNC induction: 0, 3, 30, and 180 days after induction and 210 days when the cells entered the VBNC state. Our results showed that the expression of 2,617, 2,642, 2,577, 2,829, and 2,840 genes was altered at these five different stages. The function of differentially expressed genes (DEGs, compared to healthy cells collected at day 0) and their encoded pathways were analyzed by the Gene Ontology Consortium and the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses. A total of 10 DEGs were identified in cells that entered the VBNC state: five continuously upregulated (LCAZH_0621, LCAZH_1986, LCAZH_2038, LCAZH_2040, and LCAZH_2174) and five continuously downregulated (LCAZH_0024, LCAZH_0210, LCAZH_0339, LCAZH_0621, and LCAZH_0754). Conclusions This study proposes a molecular model of the VBNC mechanism in L. paracasei Zhang, highlighting that changes in cell metabolism improve substrate utilization efficiency, thereby enhancing bacterial survival under adverse conditions. These data may be useful for improving the survival of probiotics in industrial food processing.